Interpersonal Relationships in the Contemporary 21st Century Society (InTechOpen, 2025)
In this   book, teachers, researchers, students, professionals, policymakers, and   citizens will find meaningful reflections on the (re)construction of human   relationships in today's society. The work encourages critical thinking and   dialogue about interpersonal relationships across various contexts, social   groups, and realities. Each chapter offers a thoughtful analysis of current issues impacting public life and   reflects the broader social and digital transitions shaping our global   society. The book's interdisciplinary nature, rooted in the social and human   sciences, allows for a holistic understanding of interpersonal relationships.   It contributes to the development of knowledge essential for fostering   inclusive and democratic communities and supports person-centred approaches   grounded in human rights. Human beings   are inherently social. Their ability to build and maintain relationships is   vital for promoting coexistence and solidarity. However, the nature of these   relationships is evolving—now deeply intertwined with digital practices that   reshape how we interact, communicate, and connect. As society transforms, so   must our understanding of relationships, requiring ongoing analysis and   reflection to ensure they align with core social values and promote   well-being. The transition to a   digital society poses opportunities and challenges for individuals and   businesses, as well as the fabric of human and social relationships. It   raises important questions about equal access, human connection, and   preserving meaningful family and community bonds. Ultimately, life in a 21st-century   democracy depends on promoting healthy lifestyles and reinforcing solidarity   from a humanized perspective. This includes active engagement in community   life and the work of civil society organizations whose fundamental purpose is   to nurture cohesive, compassionate, and inclusive societies.